The Association between Elevated Levels of Erythropoietin andEndothelial Progenitor Cell with Improvement of EndothelialFunction in Renal Failure Patients 3 Months after KidneyTransplantation - Armelia, Linda; Susalit, Endang; HM, Maruhum Bonar; Shatri, Hamzah (UI Scholars Hub, 2017)
Introduction. Endothelial progenitor cell (EPC) is considered possible to reduce asymmetric dimethylarginine (ADMA) levels, which is a marker of improved endothelial function. However, clinically, there is still a debate about the role of EPC. This study was conducted to determine the correlation of elevated levels of erythropoietin (Epo) and the number of EPC CD34 + and CD133 + with improvement of endothelial function in renal failure patients 3 months after kidney transplantation. Methods. A cross-sectional study was conducted in prior and 3 months after kidney transplantation of renal failure patients who underwent a kidney transplant in Cipto Mangunkusumo hospital. The study included 21 subjects who enrolled from July 2013 to February 2014. Blood samples prior and 3 months after kidney transplantation were collected to evaluate the level of Epo, numbers of EPC CD34+ and CD133+ and level of assymetric dimethylarginine (ADMA). Statistical analysis was performed using Pearson or Spearman correlation test. Results. Results of this study showed that prior to kidney transplantation, level of Epo was increased but not statistically significant (p>0.05). The EPC numbers of CD34+ and CD133+ were significantly increased (p0.05). There was no association between the elevated level of Epo and the numbers of EPC CD34+ and CD133+ with the improvement of endothelial function three months after kidney transplantation. Conclusions. In three months after kidney transplantation, there is an elevated level of Epo, the numbers of EPC CD34+ and CD133+ and decrease level of ADMA. However, there was no association between the elevated level of Epo and the numbers of EPC CD34+ and CD133+ with the improvement of endothelial function in patients 3 months after kidney transplantation.